Comparative evaluation of the antimicrobial efficacy of four chewing sticks commonly used in South India: An in vitro study - Arun Elangovan; Jayanthi Muranga; Elizabeth Joseph (Wolters Kluwer Medknow Publications, 2012)
Background and Aim: The use of chewing sticks has been well documented since ancient times in India. Chewing sticks are a good alternative to the toothbrush for maintaining oral hygiene. The present study was designed and conducted to compare and evaluate the antimicrobial effects of the aqueous extracts of neem, miswak, mango, and banyan chewing sticks against two bacterial species considered the most important in the initiation and progression of dental caries, namely Streptococcus mutans and Lactobacillus acidophilus, respectively. Materials and Methods: Twigs of the above mentioned chewing sticks were sun dried and powdered, and sterile aqueous solutions of 10%, 25% and 50% concentrations were prepared. Culture plates for S mutans and L acidophilus were prepared and the growth was transferred to nutrient agar and Mueller-Hinton agar; antimicrobial activity of the extracts was tested after 72 h, using the disc diffusion method. Normal saline was used as control. Results: The antimicrobial activity of neem, miswak, and mango extracts increased as their concentrations increased. Both banyan extract and saline showed no antimicrobial activity against the organisms tested. Conclusion and Recommendations: Based on the zones of inhibition, aqueous extracts of neem showed the most antimicrobial activity against S mutans, while miswak extracts showed superior antimicrobial activity against L acidophilus. We recommend further phytochemical and pharmacological studies to discover newer nonsynthetic tooth pastes and mouthwashes.